2008
DOI: 10.1097/fjc.0b013e318175dd73
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and the Expanding Role of Catheter Ablation: Do Antiarrhythmic Drugs Have a Future?

Abstract: The main therapeutic strategies for treating atrial fibrillation include rate control, maintenance of sinus rhythm, and antiembolic treatment. Current antiarrhythmic drugs are effective in about 50% of patients and are often associated with adverse effects. Multiple trials suggest that rate control with proper anticoagulation treatment is associated with a similar prognosis to a more aggressive rhythm control strategy. Catheter ablation of atrial fibrillation has success rates that exceed currently available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Advancing age is a major risk factor for AF and the prevalence of this condition is rising at an alarming rate with ageing of the population 1. Of the two principal options for the management of AF, rhythm control—which aims to restore and maintain sinus rhythm—is believed to be preferable to rate control, in which ventricular rate is regulated while the atria continue to fibrillate 1-3. However, currently available approaches for rhythm control have important limitations, which are discussed below, making rate control preferable in some cases, particularly in older patients with relatively few symptoms of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Advancing age is a major risk factor for AF and the prevalence of this condition is rising at an alarming rate with ageing of the population 1. Of the two principal options for the management of AF, rhythm control—which aims to restore and maintain sinus rhythm—is believed to be preferable to rate control, in which ventricular rate is regulated while the atria continue to fibrillate 1-3. However, currently available approaches for rhythm control have important limitations, which are discussed below, making rate control preferable in some cases, particularly in older patients with relatively few symptoms of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Recent small studies have suggested that atrial fi brillation ablation may result in improvements in ejection fraction, quality of life, and exercise capacity in patients with heart failure [7,8]. However, atrial fi brillation ablation has a fi rst-time effectiveness of about 65%, and patients often undergo multiple procedures, with as many as a third remaining on long-term antiarrhythmic drugs [9]. Signifi cant complications occur in up to 5% undergoing this procedure [10].…”
Section: Discussionmentioning
confidence: 99%
“…47 Moreover, because catheter ablation and surgical ablation modify the arrhythmogenic substrate, previously ineffective antiarrhythmic drugs may be reevaluated following ablation procedures. 48 Finally, the performance of antiarrhythmic, ablative, and combined rhythm-control strategies Fig. 2.…”
Section: Multichannel Blockersmentioning
confidence: 99%